Human rights and peace ideas, laws, institutions and movements - Singh, Ujjwal Kumar; Sage eBooks (Delhi ; London : SAGE, 2009)
'Human Rights and Peace' explores the shifts in the way peace has been envisaged in the rhetoric and practice of human rights.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human rights -- South Asia; Peace-building -- South Asia; Electronic books